Measuring human remains in the field: Grid technique, total station, or MicroScribe? - Sládek, Vladimír; Galeta, Patrik; Sosna, Daniel (Forensic science international, 2012)
Although three-dimensional (3D) coordinates for human intra-skeletal landmarks are among the most important data that anthropologists have to record in the field, little is known about the reliability of various measuring techniques. We compared the reliability of three techniques used for 3D measurement of human remain in the field: grid technique (GT), total station (TS), and MicroScribe (MS). We measured 365 field osteometric points on 12 skeletal sequences excavated at the Late Medieval/Early Modern churchyard in Všeruby, Czech Republic. We compared intra-observer, inter-observer, and inter-technique variation using mean difference (MD), mean absolute difference (MAD), standard deviation of difference (SDD), and limits of agreement (LA). All three measuring techniques can be used when accepted error ranges can be measured in centimeters. When a range of accepted error measurable in millimeters is needed, MS offers the best solution. TS can achieve the same reliability as does MS, but only when the laser beam is accurately pointed into the center of the prism. When the prism is not accurately oriented, TS produces unreliable data. TS is more sensitive to initialization than is MS. GT measures human skeleton with acceptable reliability for general purposes but insufficiently when highly accurate skeletal data are needed. We observed high inter-technique variation, indicating that just one technique should be used when spatial data from one individual are recorded. Subadults are measured with slightly lower error than are adults. The effect of maximum excavated skeletal length has little practical significance in field recording. When MS is not available, we offer practical suggestions that can help to increase reliability when measuring human skeleton in the field.
Keywords: soudní antropologie; odchylka pozorovatele; určení kostního věku; Bone and Bones; Reproducibility of Results; kosti a kostní tkáň; Forensic Anthropology; Regression Analysis; regresní analýza; Humans; reprodukovatelnost výsledků; Age Determination by Skeleton; Observer Variation; lidé